Synthesis of cis-5-Trifluoromethylproline from l-Glutamic Acid - Ortial, Stéphanie; Dave, Rajesh; Benfodda, Zohra; Bénimélis, David; Meffre, Patrick (Synlett, 2014)
The diastereoselective synthesis of cis-5-trifluoromethylproline (5-Tfm-Pro) from l-glutamic acid is described. 5-Tfm-Pro could be obtained through a seven-step linear sequence. Trifluoromethylation of the glutamic-derived ester or aldehyde and subsequent reduction of the cyclic imine are the key steps in the synthesis.
Keywords: amino acids; cis-5-trifluoromethylproline; fluorine; diastereoselective synthesis; imine; reduction